Sin alas a Cuban love story - Ortiz, Aruán ca. 20. Jh (Kino Lorber, Inc, 2017)
"Sin Alas, inspired by Jorge Luis Borges' short story "The Zahir," is one of the first American productions to be shot in Cuba in over fifty years. It is an epic love story that spans Cuban history from pre-evolutionary times to the modern realities of contemporary Havana. It centers on a story of lost love between Cuban writer Luis Vargas and a famous dancer named Isabella Munoz. The trajectory of Luis' life unfolds against the backdrop of modern Cuban history, from his roots in an idyllic countryside town to his current urban existence in Havana. This subtle and beautiful film explores the country and the emotional lives of its characters through a sumptuous collage of memories, places, and people." [kinolorber.com]
Original: Kuba 2015
Bonus features: behind-the-scenes featurette ; trailer
Bildformat 1.78:1 (16:9)
Keywords: Film; DVD-Video